Clima organizacional y estrés laboral en los trabajadores de la gerencia de administración de la Municipalidad Provincial de Maynas 2023 - Salinas Bicerra, Favio Gonzalo (2023)
The purpose of this research work was to determine the type of relationship between the organizational climate and work stress experienced by workers in the administration management of the Provincial Municipality of Maynas in the department of Loreto. A non-experimental cross-sectional research design was used, having a descriptive - correlational level. The research hypothesis proposed that there is an inverse and significant association between these two variables. The data collected through the completion of a survey for which a structured questionnaire was used, showed that the Pearson coefficient has a value of -0.304 with a significance of 0.020; which allows to infer that there is an inverse and significant relationship of the variables under study; which in turn, makes it possible to recommend, in a general way, that by achieving a good organizational climate, the stress level of workers decreases.